2012
DOI: 10.1016/j.virol.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of AcMNPV ac146 eliminates the production of budded virus

Abstract: Autographa californica multiple nucleopolyhedrovirus (AcMNPV) ac146 is a highly conserved gene in the Alpha- and Betabaculovirus genera that has an unknown function. Northern blot analysis and transcript mapping showed that ac146 is transcribed at late times post infection as a 1.2 kb mRNA. To determine the role of ac146 in the baculovirus life cycle ac146 knock out viruses were constructed. Transfection and plaque assays showed that all the ac146 deletions produced a single cell phenotype indicating that no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…12A). In the cases of Ac76-Cm and Cm-Ac146, two bands were detected for each construct, and this has been observed previously (39,54).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…12A). In the cases of Ac76-Cm and Cm-Ac146, two bands were detected for each construct, and this has been observed previously (39,54).…”
supporting
confidence: 82%
“…In recent years, numerous gene knockout studies have reported that certain baculovirus core genes (such as those encoding Ac76, Ac78, Ac93, Ac103, Ac142, and Ac146) are required for production of infectious AcMNPV BV. However, it is not clear how these viral proteins are involved in virus infection (34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…ac93 encodes a BV-and ODV-associated nucleocapsid protein that is present in the BV envelope fraction (33). In addition, ac9 (p78/83) (34), ac54 (vp1054) (35), ac77 (vlf-1) (36), ac98 (38k) (20), ac142 (37), and ac146 (38), which are essential for BV production, have been shown to encode nucleocapsid proteins located in both BV and ODV. Interestingly, all of these genes are not essential for …”
Section: Discussionmentioning
confidence: 99%
“…To determine the titers of infectious and noninfectious BVs released from transfected cells, the genome DNAs contained in BVs in the supernatants from the transfected cell cultures were purified and measured by real-time quantitative PCR (qPCR), as previously described (68). Briefly, 400 l of the supernatant collected from transfected cell culture was mixed with an equal volume of the lysis buffer (10 mM Tris-HCl [pH 8.0], 100 mM EDTA, 0.5% SDS, 20 g/ml RNase A, 80 g/ml protease K) and incubated at 50°C overnight.…”
Section: Methodsmentioning
confidence: 99%